System of Islamic Banking Regulation in Indonesia and Malaysia - Deanti Aulia; Amir Syafiq bin Amran (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
This study discusses the Islamic banking regulation system in Indonesia and Malaysia, two countries with the largest Muslim populations that play an important role in the development of the global Islamic finance sector. The main objective of this research is to compare and analyze the differences and similarities in Islamic banking regulations between the two countries, which have different legal backgrounds and financial systems. This study examines the legal foundations regulating Islamic banking in Indonesia and Malaysia, as well as how these regulations are implemented to support the sustainable development of the Islamic banking industry. Furthermore, this research also explores the challenges faced by both countries in ensuring compliance with Sharia principles, as well as efforts to create an inclusive and stable system in the banking sector. The novelty of this research lies in its in-depth understanding of the contextual differences in the implementation of Islamic banking regulations, as well as the comparison of policy and strategy aspects applied in Indonesia and Malaysia, providing a new contribution to the study of Islamic banking regulation in Southeast Asia.